Sodium Dodecyl Sulfate Adsorption on Sulfuric Acid-Crosslinked Chitosan/Pectin Polyelectrolyte Complex Film - Shanti, Sheila Khoirina; Aprilita, Nurul Hidayat; Siswanta, Dwi (Key Engineering Materials, 2022)
Sulfuric acid crosslinked chitosan/pectin polyelectrolyte complex (CPS) film was prepared as sodium dodecyl sulfate (SDS) adsorbent. CPS films were prepared in various compositions of chitosan/pectin and crosslinked by immersion in 0.1 M H2SO4 solution. CPS films were characterized using FTIR and SEM. CPS film was used for SDS adsorption with parameters of film composition, contact time, pH, initial SDS concentration. FTIR spectra showed characteristic peaks for chitosan, pectin, and sulfuric acid interaction. The surface of the CPS film changed to become smoother after being used for SDS adsorption. CPS film composition 70:30 showed the highest percent swelling and was stable at the overall pH. The optimum conditions for SDS adsorption by sulfuric acid crosslinked chitosan/pectin CPS film occurred at a contact time of 120 min, pH 5, initial concentration of SDS 100 mg L–1 with a film composition of 70:30. Adsorption followed the pseudo-second-order kinetic and Freundlich isotherm models with KF and n of 0.0297 and 0.377, respectively. The highest SDS desorption of 97.6% was achieved using 0.1 M NaClO4 solution.